Portfolio decision analysis methods in environmental decision making. (August 2017) - Lahtinen, Tuomas J.; Hämäläinen, Raimo P.; Liesiö, Juuso
Abstract: Environmental modellers recurrently work with decisions where a portfolio of actions has to be formed to effectively address the overall situation at hand. When creating the portfolio, one needs to consider multiple objectives and constraints, identify promising action candidates and examine interactions among them. The area of portfolio decision analysis deals with such tasks. This paper reviews portfolio modelling approaches and software that are applicable in environmental management. A framework for environmental portfolio decision analysis is provided that consists of steps ranging from problem framing to modelling and optimization, as well as to the analysis of results. The use of this framework is demonstrated with an illustrative case describing planning of urban water services. The problem is analyzed with a recently introduced portfolio decision analysis method called Robust Portfolio Modelling, which enables the use of incomplete preference information and consequence data. This feature can be particularly useful in environmental applications. Highlights: Environmental management decisions are often portfolio problems. Portfolio decision analysis offers new methods and tools to help solve these problems. A comparative description of portfolio modelling approaches is provided. A framework is developed to help the practitioner use portfolio decision analysis. An illustrative case describes a new method enabling the use of incomplete data.